Pemeliharaan Kemampuan dan Perawatan Konselor Psikologi Pegawai Negeri pada Polri (PNPP) Polda Maluku Utara Melalui Pelatihan Konseling - Yainahu, Hairani; Anggriawan, Rendy Ferdian; Nevlin, Anin Dhita Noor; Fatati, Nirmala Irianti (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
The increasing number of legal cases involving mental and psychological factors has become news consumption, it should make all levels of society aware that there are mental and psychological health problems that need to be handled seriously. Some factors that can cause mental and psychological disorders include medical factors, environmental or personal problems related to romance, family problems, to economic factors and tough life competition. Therefore, the existence of counseling training services can be a solution to connect counselors with clients. This study aims to determine the effect of counseling training on maintaining the ability and care of civil servant psychological counselors at the North Maluku Regional Police. The method used in this study is a quantitative one-group pre-test and post-test design experiment. The sample of this study was 42 civil servants at the North Maluku Regional Police (PNPP). Before being given the material, civil servants at the North Maluku Regional Police (PNPP) were given a pre-test, then after the material was completed a post-test was given to determine the personnel's understanding of counseling. The results of the analysis showed the Asymp. Sig. value. (2-tailed) is 0.020 < 0.05. This shows a significant difference between the pre-test and post-test. Therefore, it can be said that counseling training is important for maintaining the ability and care of psychological counselors for Civil Servants at the Police (PNPP) of the North Maluku Regional Police.